(untitled) (Research, Society and Development, 2022)
Introduction: Patellar tendinopathy, is an overload injury to the patellar tendon that causes disability and pain. It is a common injury in sports that include burst activities that carry the knee extension motion. Objective: To analyze the quality of evidence from clinical studies involving the use of exercise in reducing pain related to patellar tendinopathy in individuals (athletes and non-athletes). Methods: Literature search through Medline/PubMed, PEdro and Cochrane, using the following descriptors: patellar tendinopathy, (ii) pain; and (iii) exercise therapy. The PEDro rating scale was used to analyze the quality of evidence. Results: The evidence showed positive effects of isometric exercise in the short term and no difference between isometric versus isotonic exercise in the long term (0.9 NRS 95% CI 0.1 to 1.7; Post-hoc: p = 0.028). Eccentric exercise on the decline board, where it increases tension on the patellar tendon, and eccentric exercise without the medial decline board were shown to be effective in reducing pain in a 12-week program. However in another study no significant effect was found for eccentric exercise without the decline board, and there was no difference in VISA score from pre-treatment (week 1) to post-treatment (week 12; F 1.27 =0.001; P = 0.98) Conclusion: There is evidence of low to moderate methodological quality to support the short/long term effects of exercise on patellar tendinopathy pain. Better studies with fewer methodological flaws are needed.